2019
DOI: 10.1002/ps.5679
|View full text |Cite
|
Sign up to set email alerts
|

Exploiting chemical ecology to manage hyperparasitoids in biological control of arthropod pests

Abstract: Insect hyperparasitoids are fourth trophic level organisms that commonly occur in terrestrial food webs, yet they are relatively understudied. These top-carnivores can disrupt biological pest control by suppressing the populations of their parasitoid hosts, leading to pest outbreaks, especially in confined environments such as greenhouses where augmentative biological control is used. There is no effective eco-friendly strategy that can be used to control hyperparasitoids. Recent advances in the chemical ecolo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
34
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 48 publications
(39 citation statements)
references
References 65 publications
0
34
0
1
Order By: Relevance
“…Comparing egg masses parasitized by T. japonicus and T. mitsukurii , females of A. sinicus exhibited a preference in choosing T. mitsukurii volatiles. Hyperparasitoids can follow chemical cues in host location and can localize potential hosts [ 53 , 54 ]. The results obtained here showed that A. sinicus is able to use volatiles to distinguish egg masses parasitized by T. mitsukurii from those parasitized by T. japonicus or not parasitized.…”
Section: Discussionmentioning
confidence: 99%
“…Comparing egg masses parasitized by T. japonicus and T. mitsukurii , females of A. sinicus exhibited a preference in choosing T. mitsukurii volatiles. Hyperparasitoids can follow chemical cues in host location and can localize potential hosts [ 53 , 54 ]. The results obtained here showed that A. sinicus is able to use volatiles to distinguish egg masses parasitized by T. mitsukurii from those parasitized by T. japonicus or not parasitized.…”
Section: Discussionmentioning
confidence: 99%
“…A review updates what we know about oral ingestion of RNAi for insect management, including the hurdles that must be overcome to make this approach commercially viable 14 . The use of chemical ecology to manage insect parasitoids that have parasitoid hosts (fourth tropic level hyperparasitoids) is reviewed 15 . There is a review on the potential use of syrphid flies as pollinators and biological control agents 16 .…”
Section: Figurementioning
confidence: 99%
“…14 The use of chemical ecology to manage insect parasitoids that have parasitoid hosts (fourth tropic level hyperparasitoids) is reviewed. 15 There is a review on the potential use of syrphid flies as pollinators and biological control agents. 16 How climate change can affect insecticide resistance and its genetics is reviewed.…”
mentioning
confidence: 99%
“…Trophic interactions within native communities often rely on these cues, and are therefore susceptible to chemical landscape alterations that may result from the invasion of exotic insect species (Chabaane et al 2015, Rombaut et al 2017, Mair and Ruther 2019. A common third trophic level involved in plant defense are parasitic wasps -hymenopteran insects which immature life stages occur in or on other arthropods, mostly other insects- (Schultz et al 2019, Cusumano et al 2020). To nd adequate habitats for potential mates or hosts, parasitic wasps use long-range volatiles and host-associated cues from lower trophic levels (Mumm andHilker 2005, Desurmont et al 2020).…”
Section: Introductionmentioning
confidence: 99%